GLP‐1 Receptor Agonists for Type 2 Diabetes Mellitus: Recent Developments and Emerging Agents. Issue 11 (November 2014) - Trujillo, Jennifer M.; Nuffer, Wesley
<x xml:space="preserve">Abstract</x> More than 26 million people in the United States have type 2 diabetes mellitus (T2D). Many treatment options exist, but achieving long‐term glycemic control in patients with T2D remains challenging. The glucagon‐like peptide‐1 receptor agonists (GLP‐1 RAs) offer a treatment option that improves glycemic control and reduces weight, with a low risk of hypoglycemia. They have emerged as attractive options for the treatment of T2D, and significant advances and developments continue to be published regarding these agents. To identify relevant literature on emerging issues related to GLP‐1 RAs, a search of the MEDLINE database was performed. Studies published in English evaluating the safety and efficacy of GLP‐1 RAs were analyzed. Because of their advantages and unique mechanism of action, GLP‐1 RAs are currently being studied in new clinical areas, including in combination with basal insulin, as adjunctive therapy in type 1 diabetes, and for weight loss. In addition, there are several emerging agents in development. Lixisenatide is a once‐daily GLP‐1 RA that targets postprandial glucose and may be most useful when added to basal insulin as an alternative to rapid‐acting insulin. Albiglutide and dulaglutide are once‐weekly GLP‐1 RAs that may offer more convenient dosing. The most common adverse effects of all GLP‐1 RA agents are gastrointestinal (e.g., nausea, diarrhea, and vomiting), but the rates of occurrence vary among agents. Due to the differences in pharmacokinetics, efficacy, rates of adverse effects, and administration requirements within the GLP‐1 RA class, each agent should be evaluated independently. The future of GLP‐1 RAs offers broader treatment options for T2D as well as potential in other treatment areas.